COMMUNICATIVE COMPETENCIES – MODERN INSTRUMENTS UNDER ACADEMIC FREEDOMS - D.T. Ismailova; G.O. Abisheva; N.T. Ismailova; R.N.Bisenbaeva; S.S. Mazhikeeva (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses communication skills, language competencies, which are the main mechanism for the effective activity of an individual in a sociocultural and multilingual world. Learning a foreign language is a priority in preparing future specialists for the challenge of time and society. With this situation in the current world situation, it is extremely necessary to develop methods for the development of communicative skills in a psychological aspect, while, first of all, we are talking about the necessary optimization of the spent human and time resources aimed at success. The problem of the formation of students’ communicative competence in the psychological aspect is the main criterion that must be taken into account when entering into intercultural communication, this can be seen in almost all studies, while students are the main object of study.